Maternal cardiopulmonary resuscitation. Issue 1 (18th October 2022) - Tanaka, Hiroaki; Matsunaga, Shigetaka; Furuta, Marie; Kato, Rie; Takahashi, Shinji; Takeda, Jun; Nakao, Masahiro; Nakamura, Eishin; Nii, Masafumi; Yamashita, Tomoyuki; Yamahata, Yoshihiro; Enomoto, Naosuke; et al.
Abstract: The perinatal resuscitation history in Japan is short, with the earliest efforts in the field of neonatology. In contrast, the standardization and dissemination of maternal resuscitation is lagging. With the establishment of the Maternal Death Reporting Project and the Maternal Death Case Review and Evaluation Committee in 2010, with the aim of reducing maternal deaths, the true situation of maternal deaths came to light. Subsequently, in 2015, the Japan Council for the Dissemination of Maternal Emergency Life Support Systems (J‐CIMELS) was established to educate and disseminate simulations in maternal emergency care; training sessions on maternal resuscitation are now conducted in all prefectures. Since the launch of the project and council, the maternal mortality rate in Japan (especially due to obstetric critical hemorrhage) has gradually decreased. This has been probably achieved due to the tireless efforts of medical personnel involved in perinatal care, as well as the various activities conducted so far. However, there are no standardized guidelines for maternal resuscitation yet. Therefore, a committee was set up within the Japan Resuscitation Council to develop a maternal resuscitation protocol, and the Guidelines for Maternal Resuscitation 2020 was created in 2021. These guidelines are expected to make the use of high‐quality resuscitation methods more widespread than ever before. This presentation will provide an overview of the Guidelines for Maternal Resuscitation 2020.